HYGIENIC ASSESSMENT OF SCHOOL STUDENTS' NUTRITION - Salomova F. I.; Khakimova D. S. (The Conference Hub, 2025)
During the period of education in general secondary schools, students are engaged in both mental and physical activities. As a result, they expend a significant amount of energy and require foods with high energy value. Students spend between 6 to 8 hours per day at school, and their proper nutrition during this time plays a crucial role in maintaining their health.Improper organization of students' nutrition in general education schools reduces their bodies' ability to cope with environmental factors. Inadequate or unbalanced nutrition negatively impacts not only their learning and cognitive abilities, but also their growth and overall health.